PERTAUBATAN WANITA PEKERJA SEKS KOMERSIAL (PSK) DI MAJELIS ASY-SYIFA (STUDI BIMBINGAN SOSIO-SPIRITUAL) - Titik Rahayu (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2018)
Commercial sex workers often get rejection, discrimination and negative stigmatization from the community. Even so, there are still many women in Indonesia who work as commercial sex workers. Among them are some commercial sex workers who want to repent and get out of prostitution. This article focuses on describing the efforts of commercial sex workers so that they have the awareness and determination to repent. The use of descriptive qualitative methods on the subject of research originating from former commercial sex workers and guidance counselors suggests that the guidance model implemented in the Asy-Syifa Assembly by combining social and spiritual aspects is capable of motivating commercial sex workers to repent. Implementation of socio-spiritual guidance is manifested through the provision of knowledge, attitude and social interaction, as well as support in the form of advice and motivation.